Robotic-assisted right medial and anterior basal segmentectomy (S7+S8) - Li, Jian-Tao; Huang, Jia; Luo, Qing-Quan (Journal of Thoracic Disease, 2018)
Anatomical segmentectomy for medial (S7) and anterior basal segments (S8) is still challenging even with substantial progress in surgical technique over these years. We believe that segmentectomy could be much more comfortable with the application of the da Vinci surgical system in thoracic surgery. With nearly 10-year experience of robotic thoracic surgery, we gradually develop a new way of port placement and surgery. Here we present a step-by-step right medial and anterior basal segmentectomy (S7+S8) with a high-quality video and preference cards.